2009
DOI: 10.1007/s00167-009-0958-y
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory effects of topical glyceryl trinitrate on the Achilles tendon microcirculation in patients with previous Achilles tendon rupture

Abstract: Topical glyceryl trinitrate treatment has demonstrated short- to mid-term efficacy in chronic noninsertional Achilles tendinopathy. However, the underlying mechanisms are far from being understood. We hypothetized that Achilles tendon capillary blood flow changes immediately after topical glyceryl trinitrate treatment. Fifteen patients (55 + or - 15 years, VAS 5.8 + or - 2.3) with current mid-portion Achilles tendon pain 36 months after open surgical Achilles tendon repair for tendon rupture were included. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The StO 2 values in the repaired Achilles tendons were only significantly greater than those in the noninjured tendons at 3 months after surgery (Table 2). Our findings regarding the THb levels support those of a previous study, which found greater capillary blood flows in the repaired tendon among subjects at an average time point of 3 years after surgery [5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The StO 2 values in the repaired Achilles tendons were only significantly greater than those in the noninjured tendons at 3 months after surgery (Table 2). Our findings regarding the THb levels support those of a previous study, which found greater capillary blood flows in the repaired tendon among subjects at an average time point of 3 years after surgery [5].…”
Section: Discussionsupporting
confidence: 91%
“…To the best of the authors' knowledge, only a single previous study has used near‐infrared spectroscopy to observe tendon microcirculation in repaired Achilles tendons in humans and found that capillary blood flows in repaired tendons were greater than those in uninjured tendons at an average of 3 years after surgery [5]. More studies in humans are required to prove these findings from the studies in animals mentioned previously.…”
Section: Introductionmentioning
confidence: 98%
“…Acute GTN facilitates capillary venous outflow in painful Achilles tendons. However, in another study, capillary blood-flow and tendon oxygenation remain unchanged following GTN application [88]. A randomized double-blind placebo-controlled study demonstrated improvements in symptoms using GTN patches [89].…”
Section: Treatmentmentioning
confidence: 99%
“… 16) It is believed that it increases collagen production by fibroblasts, cellular adhesion, and local vascularity. However, a study by Osadnik et al 17) concluded that a topical glyceryltrinitrate facilitates capillary venous outflow in painful Achilles tendons and that the capillary blood flow and tendon oxygenation remain unchanged. In a randomized double-blind placebo-controlled study by Hunte and Lloyd-Smith, 18) a topical glyceryltrinitrate patch was more effective than placebo for reducing pain from chronic non-insertional Achilles tendinosis in the first 12 and 24 weeks of use.…”
Section: Conservative Treatmentmentioning
confidence: 99%